GAMBARAN PERAN SERTA PETUGAS KESEHATAN TERHADAP KEPATUHAN BEROBAT PENDERITA TB PARU DI KELURAHAN GAMBIR BARU KECAMATAN KISARAN TIMUR TAHUN 2014 - Pandapotan Sormin; Kintoko Rochadi; Alam Bakti Keloko (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
Pulmonary Tuberculosis is an infectious disease caused by the bacteria directly with pulmonary tuberculosis (mycobacterium tuberculosis lung). Most of pulmonary TB germs attack lungs, but can also regarding another parts of body. East Kisaran district is one of the District in shavings with cases of TB patients are quite high. Where every year the number of TB cases is still on the charts high enough. In 2010 a total of 36 cases increased to 40 cases in 2011, then increased to 41 cases in the following year in 2012 and the last in 2013 to 40 cases. This research is a descriptive survey aimed to determine the role of Officer of Health for treatment compliance in patients with pulmonary tuberculosis in Gambir Baru subdistrict East Kisaran District of the Year 2014. The entire range of pulmonary tuberculosis patients who passing the treatment period of at least 6 months in Gambir Baru subdistrict East Kisaran district in 2014 as many as 43 people. Sampling was done by (total sampling) TB patients who undergo treatment as many as 43 people. The results showed that the Trustees took the drug for treatment compliance respondent is good for 22 persons (51.2%), Health Extension of the respondent is a good treatment compliance is 29 persons (44.2%), Interpersonal Communication on TB treatment compliance is good that 20 people (46.5 %), Motivation Officer of Health for TB treatment compliance is sufficient that 20 people (46.5%), TB treatment compliance respondents were adherent of 28 people (65.1%) Based on the research results suggested increase counseling and manufacture of pamphlets, and billboards to increase public knowledge about the prevention of pulmonary TB, the community to participate in pulmonary tuberculosis disease prevention programs   Keywords: pulmonary tuberculosis patients, TB